FiMoDeAL: pilot study on shortest path heuristics in wireless sensor network for fire detection and alert ensemble - Ifeanyi Akazue, Maureen; Efetobore Edje, Abel; Okpor, Margaret Dumebi; Adigwe, Wilfred; Ejeh, Patrick Ogholuwarami; Odiakaose, Christopher Chukwufunaya; Ojugo, Arnold Adimabua; Edim, Edim Bassey; Ako, Rita Erhovwo; Geteloma, Victor Ochuko (Bulletin of Electrical Engineering and Informatics, 2024)
With the incessant outbreak of fire, the heavy loss to both lives and properties in the society fire has since become a critical issue and challenge that needs our daily attention to be resolved. Loss of lives and properties to fire outbreak in 2021 alone as occurring in major Nigerian markets and residential homes was estimated at over 3 trillion Naira. Our study proposes a wireless sensor network internet of things (IoT) based ensemble to aid the effective monitoring, detection and alerting of residents and fire service departments. With cost as a major issue and the requisite installation of fire and smoke detectors in many houses our ensemble can efficiently integrate into the existing system using the ESP8285-controller to create a comprehensive access control system. The system provides real time monitor and control capabilities that will allow administrators to track and manage fire monitor and detection within a facility. Thus, enhances system's efficiency and performance.